On the economics of CO2 contracts in the enhanced oil recovery industry - Shen Gao; Chenghan Hou; Long Zhao (Journal of Applied Economics, 2022)
While Carbon Dioxide based Enhanced Oil Recovery (CO2 -EOR) is often regarded as one of the most economically viable methods of carbon capture, utilization and storage (CCUS), little is known about the existing CO2 supply contracts in the CO2 -EOR industry. By studying a sample of 103 CO2 sales contracts in the U.S. in the 1980s and 1990s, this paper aims to find out what drives the key terms in these contracts. In particular, a special price adjustment clause is included to peg the CO2 price to the oil price. Our analyses suggest that the probability that the pegging term is used is positively associated with the contract length. Besides, initial oil prices, volatile historical oil prices, and the net CO2 utilization also positively impacts the adoption of the price-pegging adjustment mechanism.
Keywords: 330; Carbon dioxide based enhanced oil recovery; CO2 prices; price adjustment clause